CASE STUDIES OF TOGOLESE KARATE FEDERATION "FTK" TOURNAMENTS: LESSONS FROM THE IMPACT AND MANAGEMENT OF EVENTS IN SPORTS ASSOCIATIONS IN TOGO - Amavi, Ayi kokou (Πανεπιστήμιο Πελοποννήσου, 2022)
Sporting activities generally offer young people and older people in our countries an appropriate framework for exercising all kinds of physical and sporting activities to express their motor skills in order to keep fit. The desire to keep fit is not only the reason why young people practice physical exercise, but also the desire to practice sport as a profession or to develop their skills in order to participate in competitions or tournaments organized by sports associations or federations. Thus, in terms of competition, some sportsmen and women compete in tournaments. These sports tournaments are organized by sports associations in Togo periodically according to a plan that gives them a certain image. The associations individually organize tournaments in their discipline according to a certain organization of their own. Thus, at the level of martial arts federations, the Togolese Karate Federation also organizes tournaments in the city of Lomé and in the interior of the country. The aim of our project is to review some of the tournaments that the Togolese Karate Federation has already organized; especially the tournaments of July 2011, July 2014 and December 2017; to analyze how these tournaments were organized before, during and after the event with the aim of observing their real impact and to see how these events can be improved on certain aspects. Following this analysis, we will draw concrete conclusions. This analysis, which will focus on three tournaments, will lead us to propose a guide for organizing sports events to the Togolese Karate Federation, which will also serve as a reference for other associations or sports federations that do not have a guide for organizing sports events. During our research, we were confronted with the reality that there were real organizational shortcomings in the setting up and realization of FTK tournament projects. This led us to make recommendations and to propose a guide for the organization and management of sports events.
Keywords: Πολεμικές τέχνες για παιδιά; Πολεμικές τέχνες - Τουρνουά; Φυσική κατάσταση; Αθλητικά γεγονότα - Διοίκηση και οργάνωση; Martial arts for children; Martial arts - Tournaments; Physical fitness; Sports events - Management; Karate tournaments; Organization of sports; Management of sports